Brain iron burden is associated with accelerated cognitive decline in Alzheimer's disease: Human neuropathology: AD neuropathology. (7th December 2020) - Ayton, Scott; Portbury, Stuart; Kalinowski, Pawel; Diouf, Ibrahima; Agarwal, Puja; Schneider, Julie A.; Morris, Martha Clare; Bush, Ashley I.
Abstract: Background: Brain iron has been reported elevated in Alzheimer's disease (AD) in mostly small studies that were without extensive clinicopathological classification. Brain iron may be important for disease progression since it can become pro‐oxidant and induce cell death (by ferroptosis) or inflammation (by promoting an inflammatory phenotype of microglia). Here, we report the largest post‐mortem study of brain iron in AD, examining iron in multiple brain regions in a large (645) group across the clinicopathological staging of the disease with extensive cognitive data collected in the decade prior to death. Methods: Iron was measured in gray matter from inferior temporal, mid frontal, anterior cingulate, and cerebellar cortices from 645 post‐mortem brains (Memory and Aging Project). AD pathology was defined by CERAD criteria. NINCDS‐ADRDA criteria were used to assign AD clinical diagnosis during life. Cognitive performance (test batteries for multiple cognitive domains) was assessed annually in the decade prior to death. Analysis consisted of mixed‐effects models with quadratic and linear variables: iron, age, sex, APOE ε4, plaque counts, neurofibrillary tangle counts, Lewy bodies, vascular infarcts. Results: This study included 166 pathology‐negative subjects without dementia, 40 pathology‐negative subjects with dementia, 212 subjects with AD pathology but without dementia, and 227 subjects with AD pathology and dementia. In subjects without dementia, iron levels were not associated with pathological status, demonstrating that iron does not elevate in the brain merely with increasing pathology load. Iron was elevated (p = 2 × 10 −4 ) in the inferior temporal cortex of people with AD pathology and clinical dementia, but not in any other region. Nonetheless, the iron status of each region was strongly associated with accelerated cognitive decline in the years prior to death, regardless of whether iron was increased, with a composite of iron values in each region demonstrating the greatest performance (Figure 1). Conclusions: Iron is regionally elevated in AD brains, but, importantly, iron need not be increased to pathological levels to influence neurodegeneration. Rather, iron burden acts as a risk factor trait in brains with iron levels in the normal range.